ART AND ARCHITECTURE OF ANCIENT KASHMIR DURING KARKOTA DYNASTY WITH SPECIAL REFERENCE TO LALITADITYA MUKTAPIDA (724-761 A.D) - Shabir Ahmad Lone (RADJA PUBLIKA, 2026)
The Karkota dynasty of Kashmir reached its zenith under the reign of Lalitaditya Muktapida (724–761 A.D.), widely regarded as its most illustrious ruler. His reign marked a golden age in the political, cultural, and artistic history of Kashmir. Lalitaditya’s achievements were remarkable not only for his extensive military campaigns, which earned him enduring historical recognition, but also for his enlightened governance. He pursued a policy of religious tolerance, extending patronage to both Buddhism and Brahmanism by commissioning temples, monasteries, and viharas that became important centres of learning. Scholars from within and beyond the region were welcomed and generously supported, fostering a vibrant intellectual environment. The administration undertook significant public works, including the improvement of infrastructure, irrigation facilities, and relief measures during natural calamities. Charitable institutions ensured regular support for the poor and destitute. Often described by historians as the “Alexander of Kashmiri history” or the “Samudragupta of Kashmir,” Lalitaditya presided over a flourishing of art, architecture, culture, and learning. This study examines the artistic and architectural traditions of the Karkota period, emphasizing their enduring significance within India’s cultural heritage.